A narrative review of nonspecific effects of pediatric vaccines on child mortality and morbidity - Muna Omar; Khitam Muhsen (Taylor & Francis Group, 2021)
We reviewed evidence on nonspecific effects of pediatric vaccines on mortality and morbidity in countries with high child mortality. Literature search of epidemiological studies was conducted for studies published between 2000 and September 2021 using MEDLINE. Consistent evidence exists regarding the potential protective effect of measles vaccine on child survival. Vaccination with Bacillus Calmette-Guérin (BCG) vaccine was related to lower risk of mortality in young children (including low birth weight babies) and inverse associations were found between developing a scar and having a positive tuberculin test after BCG vaccination with mortality. BCG vaccine might also reduce the risk of nontuberculosis infectious diseases. Studies on the association between diphtheria-pertussis-tetanus (DPT) vaccine and child survival showed inconsistent findings, which might be affected by bias and confounding. More evidence is needed to assess the role of these and other vaccines in children's health and to better understand potential biological mechanisms and other influential factors.